1999
DOI: 10.1016/s0896-6273(00)80734-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased Activity in Human Visual Cortex during Directed Attention in the Absence of Visual Stimulation

Abstract: When subjects direct attention to a particular location in a visual scene, responses in the visual cortex to stimuli presented at that location are enhanced, and the suppressive influences of nearby distractors are reduced. What is the top-down signal that modulates the response to an attended versus an unattended stimulus? Here, we demonstrate increased activity related to attention in the absence of visual stimulation in extrastriate cortex when subjects covertly directed attention to a peripheral location e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

135
1,142
19
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,483 publications
(1,305 citation statements)
references
References 56 publications
135
1,142
19
9
Order By: Relevance
“…We propose that, together with the SPL, it serves to maintain a spatiotemporal bias against to-be-ignored locations, in favor of to-be-searched locations. In all, the parietal activation is reminiscent of activation found in numerous neuroimaging studies as part of an emerging general top-down frontoparietal attention network [for reviews see Corbetta, 1998;Kanwisher and Wojciulik, 2000;Kastner et al, 1999]. It provides support for the idea that observers actively bias attention toward the new items in the preview task.…”
Section: Discussion Previewmentioning
confidence: 66%
See 2 more Smart Citations
“…We propose that, together with the SPL, it serves to maintain a spatiotemporal bias against to-be-ignored locations, in favor of to-be-searched locations. In all, the parietal activation is reminiscent of activation found in numerous neuroimaging studies as part of an emerging general top-down frontoparietal attention network [for reviews see Corbetta, 1998;Kanwisher and Wojciulik, 2000;Kastner et al, 1999]. It provides support for the idea that observers actively bias attention toward the new items in the preview task.…”
Section: Discussion Previewmentioning
confidence: 66%
“…In a functional magnetic resonance imaging (fMRI) study on humans, Coull and Nobre [1998], using a combined spatial/temporal cueing task, found parts of the intraparietal sulcus (IPS) and superior parietal lobule (SPL) to be active during spatial orienting, temporal orienting, or the combination of spatiotemporal orienting. Other neuroimaging studies have found the SPL to respond mainly to the cue rather than to the target, suggesting that it is involved in setting up or maintaining an expectation, in anticipation of the target [Corbetta, 1998;Kastner et al, 1999;Shulman et al, 1999]. The same conclusion can be reached based on patient studies indicating that the posterior parietal lobe is crucial in setting up, maintaining, or disengaging spatial attention [Friedrich et al, 1998;Posner et al, 1984Posner et al, , 1987.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Extensive activations also involved the medial occipital lobes (cuneus and lingual gyrus) bilaterally, extending anteriorly into the precuneus and posterior parahippocampal gyrus. These medial occipital activations, which likely reflect shifts of attention from foveal to peripheral visual locations (Brefczynski & DeYoe, 1999;Kastner et al, 1999;Tootell et al, 1998), are not relevant to the aims of this study and will not be discussed further. Additional activations involved the left frontoparietal operculum and supramarginal gyrus, right dorsal prefrontal cortex (MFG and superior frontal sulcus), bilateral suborbital sulcus and gyrus rectus, left orbitofrontal cortex (OFC), left mid-cingulate gyrus, and right angular gyrus.…”
Section: Fmrimentioning
confidence: 99%
“…Under conditions of low stimulus visibility, for example, human subjects generate preparatory signals in visual cortex, and variability in these preparatory signals at the time of target presentation predicts accuracy of stimulus detection (Ress, Backus, & Heeger, 2000) 1 . Preparatory signals also seem to be modulated by spatial attention (Corbetta, Kincade, & Shulman, 2002;Jack, Shulman, Snyder, McAvoy, & Corbetta, 2006;Kastner, Pinsk, De Weerd, Desimone, & Ungerleider, 1999;Serences, Yantis, Culberson, & Awh, 2004). Preliminary evidence suggests that one function of preparatory signals may be to reduce external noise (Serences et al, 2004).…”
mentioning
confidence: 99%